(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2025)
A long-standing custom is to produce new items throughout the course of time. As time goes on, the health care system is likewise undergoing change. In order to strengthen the health care system through the use of techniques that are supported by evidence, researchers are always paying attention. In the course of our ongoing attempts to discover answers to difficult challenges in the healthcare industry, artificial intelligence is becoming an increasingly acceptable tool. Researchers have been able to recognise certain patterns in enormous complicated data sets that were previously thought to be buried as a result of the development of new technology in the disciplines of data science and data analysis. All of these cutting-edge techniques, in conjunction with the increasing processing capacity of computers, make it possible for the healthcare system to function with greater precision and efficiency. It is imperative that artificial intelligence be included into nursing science and the health care system in order to make any uncertainties clear and to satisfy the requirements of advanced nursing care. The transformation of these extended technologies is going to be carried out for the benefit of patients. In spite of the fact that there are some great outcomes, artificial intelligence technology also has certain negative repercussions that might have a detrimental impact on the nursing profession. Exploring and discussing the influence that artificial intelligence has had on nursing care, the healthcare system, nursing education, and nursing research was the purpose of this.